FUNGSI WACANA HUMOR STAND-UP COMEDY DI INDONESIA (Lingua, 2020)
Stand-Up Comedy is one type of humor show that has now developed throughout the world to become a creative industry. Stand-up comedy is an entertainment that until now is still in demand by all ages and segments of society. The material delivered by Komika can provide entertainment to the audience as well as a medium of social criticism and education for the community. The research data was obtained from stand-up comedy shows on several television stations in Indonesia, which were analyzed qualitatively to provide relevant data to reveal the function of stand-up comedy humor. The results showed that in general the material of stand-up comedy humor has the main function as a means of recreation or entertainment, while secondary functions include educational functions, mock/ quip function, power function, persuasive functions, solidarity functions, psychological functions, and communication functions.